Family functioning assessment in the context of mental health (Archives of Clinical Psychiatry, 2011)
OBJECTIVE: To determine which instruments have been used in the assessment of family functioning in the context of mental health. METHOD: Systematic review according to Cochrane standards in databases: Medline, PubMed and PsycInfo from January 1990 to July 2009. We considered articles in English, Portuguese and Spanish who presented the use of scales, questionnaires and interviews in the assessment of family relationship in the context of mental health. The abstract should specify the name of the instrument, applying at least two family members, to present objective, methodology and results. The keywords used were: family functioning and assessment and psychiatry. RESULTS: This study found 1,162 articles and 20 were selected. The instruments cited were: Family Assessment Device (FAD), Family Environment Scale (FES), Family Assessment Measure (FAM) Family Adaptability and Cohesion Evaluation Scale III (FACES III). The most families dysfunctions were related to: the performance of roles, norms and values, communication, affective involvement and problem resolution. The improvement of family functioning was associated with recovery of patients with mental disorders. DISCUSSION: The use of family assessment instruments can contribute to the planning of therapeutic interventions and rehabilitation in mental health.